Redescription of the freshwater amphipod Hyalella faxoni from Costa Rica (Crustacea: Amphipoda: Hyalellidae) - González, Exequiel R; Watling, Les (Revista de Biología Tropical, 2002)
Hyalella faxoni Stebbing, 1903 from Costa Rica is redescribed. The species was previously in the synonymy of Hyalella azteca (Saussure, 1858). The morphological differences between these two species are discussed.